Pengaruh Kepemimpinan Islami dan Budaya Organisasi Islami Terhadap Motivasi Kerja Islami Pada UMKM Kulit di Magetan - Rezy Aziz; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The purpose of this research is to know the effect of islamic leadership and islamic organization culture in variable through islamic work motivation to SMEs leather in Magetan.This research uses questionnaires in primary data collected and the method used is quantitative descriptive by using two independent variables islamic leadership and islamic organization culture and a dependent variable islamic work motivation. Research sampling is the employee of SMEs leather in Magetan industry area in east java, it was 110 people. Sampling collected takes in proportioned stratified random sampling because each SMEs leather will be taken a random sampling. Data analysis technique used is multiple linear regression analysis by using F and T treatment as hypothesisThe results showed that simultaneous and partial Islamic leadership and Islamic organizational culture influence significant on Islamic work motivation. REFERENCESAbbassi, R. d. 2009. Propensities of Tajik, Uzbek and Russians Towards Islamic Work Ethics. Journal of Qafqaz University.Ahmad, Khaliq. 2009. Leadership and Work Motivation from the Cross Cultural Perspective. International Journal of Commerce and Management. Volume 19 No. 1 2009.___________. 2007. Management From Islamic Perspective: Principle and Practice. Malaysia: Research Centre International Islamic University Malaysia .___________.2011. An empirical assessment of Islamic leadership principles. International Journal Commerce and Management. Volume 21 No.3 .Arep, Ishak dan Hendri Tanjung. 2003. Manajemen Motivasi. Jakarta: PT.Gramedia Widiasarana Indonesia.Arikunto, Suharsimi. 2004. Prosedur Penelitian Suatu Pendekatan Praktek. Bandung: Rineka Cipta.Azis, Abdul Wahab. 2008. Anatomi Organisasi dan Kepemimpinan Pendidikan. Bandung: Alfabeta.Danim, Sudarman. 2004. Motivasi Kepemimpinan dan Efektivitas Kelompok. Jakarta: PT. Rineka Cipta.Friska. 2004. Kepemimpinan dalam Organisasi. dalam http://digilib.usu.ac.id/ download/fe/manajemenfriska.pdf, diakses tanggal 30 April 2013.Ghozali, Imam. 2006. Aplikasi Analisis Multivariate dengan Progam SPSS. Semarang: Universitas Diponegoro.Hakim, Abdul. 2007. Kepemimpinan Islami. Semarang: Unissula Press.___________. 2012. The Implementation of Islamic Leadership and Islamic Organizational Culture and Its Influence on Islamic Working Motivation and Islamic Performance PT. Bank Mu’amalat Indonesia Tbk. Employee in the Central Java. Asia Pacific Management Review17 (1) (2012) 77-90.Hariandja, Marihot TE. 2002. Manajemen Sumber Daya Manusia. Jakarta: GrasindoHasan, Dede. 2002. Kemampuan Manajerial Pimpinan dalam Memotivasi dan Mendisiplinkan Karyawan dikaitkan dengan Produktivitas Kerja. Bandung: PPs UPI.Kriyantono, Rahmat, 2006, Teknik Praktis Riset Komunikasi, Jakarta: PT Kencana Prenada Media Group.Koesmono, H. T. 2010. Pengaruh Budaya Organisasi Terhadap Motivasi Dan Kepuasan Kerja Serta Kinerja Karyawan Pada Sub Sektor Industri Pengolahan Kayu Skala Menengah Di Jawa Timur. Ekonomi Manajemen.Maghfiroh, Siti. 2012. Pengaruh Kepemimpinan Islami dan Motivasi Kerja Terhadap Kinerja Karyawan di Lembaga Keuangan Syari’ah KJKS Kabupaten Kendal (Studi Kasus KJKS di Kecamatan Rowosari dan Weleri). Skripsi. Semarang: Institute Agama Islam Negeri Walisongo.Majeed, Yasir & Khaliq, Zulqarnain. 2011. The Impact of Islamic Leadership on Organizational Objectives. Far East Journal of Marketing and Management. Volume 1 No.1.Mulianto, S. 2006. Panduan Lengkap Supervisi Diperkaya Perspektif Syariah. Jakarta: Gramedia Pustaka Utama.Nawawi. 2003. Metode Penelitian Bidang Sosial. Yogyakarta: Gajah Mada University PressOmer, Zaneb & Omar, Syed. 2012. The Effects of Islamic Management Ethics on Organizational Commitment of Employees in Libyan Public Bank. Australian Journal of Basic and Apllied Sciences,6(7):260-270.Pramandhika, Ananto. 2011. Motivasi Kerja Islami (Studi Kasus pada Guru TPQ di Kecamatan Semarang Selatan). Jurnal Universitas Diponegoro.Rizqi, Maudidyah Amalia. 2010. Analisis Model Kepemimpinan Islami Pada CV. Dharma Utama Batu. Malang: UIN Maulana Malik Ibrahim.Robbins, Stephen P. 2006. Perilaku Organisasi. Jakarta: PT. Indeks Kelompok Gramedia.Sardiman. 2007. Interaksi dan Motivasi Belajar Mengajar. Jakarta: PT. RajaGrafindo Persada.Silalahi, Ulber. 2002. Pemahaman Praktis Asas-asas Manajemen. Bandung: Mandar Maju___________. 2009. Metode Penelitian Sosial. Bandung: PT.Refika Aditama.Singodimedjo, Markum. 2002. Manajemen Sumber Daya Manusia. Surabaya: SMMASSobirin, Achmad. 2007. Budaya Organisasi. Yogyakarta. YKPN. Sugiyono. 2008. Statistika untuk Penelitian. Bandung: Alfabeta.Suryati. 2010. Pengaruh Kompensasi Terhadap Motivasi Kerja. Jurnal Mimbar Bumi Bengawan.Susanto, H., & Aisiyah, N. 2010. Analisis Pengaruh Kepemimpinan dan Budaya Kerja dengan Motivasi sebagai Variabel Intervening terhadap Kinerja Karyawan di Kantor Pertanahan Kabupaten Kebumen. Magistra No. 74.Sutrisno, Edy. 2010. Budaya Organisasi. Jakarta: Kencana.Tasmara, Toto. 2006. Spiritual Centered Leadership-Kepemimpinan Berbasis Spiritual. Jakarta: Gema Insani.Utami, I. T. 2007. Pengaruh Gaya Kepemimpinan Transformasional Terhadap Motivasi Kerja Karyawan Pada PT Trade Servistama Indonesia-Tangerang. Ekonomi dan Manajemen.Uyanto, Stainlaus S. 2006. Pedoman Analisis Data dengan SPSS. Yogyakarta: Graha Ilmu.www.depkop.go.id diakses pada tanggal 21Juni 2013.www.immasjid.com diakses tanggal 9 April 2013.Zahro, Najmatuz. (2005). Pengaruh Gaya Kepemimpinan Terhadap Semangat Kerja Karyawan Pada KUD DAU Malang. Skripsi. Malang: FE